2023
DOI: 10.3390/su15053897
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Differentiation and Driving Factors of Carbon Storage in Cultivated Land-Use Transition

Abstract: Revealing the response of carbon storage to cultivated land-use transition (CLUT) and identifying its driving factors are of great significance for maintaining ecosystem stability and promoting regional carbon peak and carbon neutrality goals. Given the knowledge gap regarding the driving factors of carbon storage in CLUT, this study takes the Songhua River Basin in the black soil region of China as the case study area. The study aimed to reveal the spatial–temporal heterogeneity of carbon storage in CLUT base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The model allows for the addition of future spatial policy elements, which can more scientifically simulate future LUCC under different policy scenarios [10,11]. Previous research has explored the influence of LUCC on carbon storage, including national [12], provincial [13], urban agglomeration [14,15], arid area [16], watershed [17,18], coastal zone [19], city [20,21], and county [22] scales. In summary, the existing research has extensively discussed the influence of LUCC on carbon storage and predicted future changes in carbon storage.…”
Section: Introductionmentioning
confidence: 99%
“…The model allows for the addition of future spatial policy elements, which can more scientifically simulate future LUCC under different policy scenarios [10,11]. Previous research has explored the influence of LUCC on carbon storage, including national [12], provincial [13], urban agglomeration [14,15], arid area [16], watershed [17,18], coastal zone [19], city [20,21], and county [22] scales. In summary, the existing research has extensively discussed the influence of LUCC on carbon storage and predicted future changes in carbon storage.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, cultivated land is also considered a carbon source. Due to the high density of human activities on cultivated land, the carbon emission coefficient is not stable and needs to be determined by linear regression based on historical data [34]. The carbon emission factor of cultivated land in Guangzhou in 2035 is calculated as 181.735 t/km 2 .…”
Section: Relationship Between Land Use and Carbon Emissionsmentioning
confidence: 99%
“…With the expansion of construction land, the encroachment of ecological space and growth in energy consumption sharply increase the carbon emissions [38]. The carbon emissions from construction land can be accounted by a mature methodological system and have been proven to be in a constant state of change by existing studies [34,39,40]. Thus, the time series pattern of carbon emissions from construction land needs to be explored based on historical carbon emissions to determine future carbon emissions.…”
mentioning
confidence: 99%
“…The research shows that ecological construction and scientific and technological progress are important reasons for the improvement of EEQ, while population and economic development are the reasons for the deterioration of EEQ. Gai Zhaoxue 16 used geographical detectors to explore and find that the distance from water and road is an important factor affecting the spatial differentiation of EEQ in the Songhua River basin. Through the combination of Pearson correlation analysis and geographic detector 17 , it is concluded that the topographic factor is the main reason that affects the spatial differentiation of EEQ in the north-south transition zone of China.…”
Section: Introductionmentioning
confidence: 99%